2018
DOI: 10.4274/jcrpe.0121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical characteristics of the patients with Vitamin D Dependent Rickets Type 1A

Abstract: Objective: Vitamin D dependent rickets type 1A (VDDR1A) is an autosomal recessive disorder caused by mutations in the 25OHD 1α-hydroxylase gene (CYB27B1). As it may be confused with nutritional rickets and hypophosphatemic rickets, genetic analysis is important for making a correct diagnosis. Methods: We analysed genomic DNA from 11 patients from 8 different Turkish families. The patients were recruited for our studies if they presented with diagnosis of vitamin D dependent rickets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The finding of bone deformities due to disruption of bone mineralization in the area of the growth plate is a hallmark of rickets, the most common form of which is nutritional related (10). In general, impaired vitamin D metabolism is associated with four types of rickets, including VDDR1A, VDDR1B, VDDR2A or VDDR and VDDR2B, and is characterized by defects in proper expression of CYP27B1, CYP2R1, vitamin D receptors, and protein related to vitamin D receptor function, respectively (1,11). Pseudo-VDDR (PDDR) or VDDR1 presented with hypotonia, hypoplasia of dental enamel, growth retardation, weakness, and developmental delay at the age of 6-24 months.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of bone deformities due to disruption of bone mineralization in the area of the growth plate is a hallmark of rickets, the most common form of which is nutritional related (10). In general, impaired vitamin D metabolism is associated with four types of rickets, including VDDR1A, VDDR1B, VDDR2A or VDDR and VDDR2B, and is characterized by defects in proper expression of CYP27B1, CYP2R1, vitamin D receptors, and protein related to vitamin D receptor function, respectively (1,11). Pseudo-VDDR (PDDR) or VDDR1 presented with hypotonia, hypoplasia of dental enamel, growth retardation, weakness, and developmental delay at the age of 6-24 months.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Case reports of VDDR-1A, like in our patients, have been published recently, emphasizing that 1.25(OH)2D levels can be within normal ranges and this may explain difficulties in making the diagnosis. [11][12][13][14][15] On the other hand, VDDR-2 is characterized by resistance to 1.25 (OH) 2 D because of pathogenic variants in VDR (vitamin D receptor gene, VDDR-2A) or the overexpression of a nuclear ribonucleoprotein that interferes with vitamin D receptor-DNA interaction (VDDR-2B). 2,3 In these cases, 25(OH)D can be within normal or increased levels and 1.25(OH) 2 D is usually increased.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP27B1 gene is constituted of 9 exons spanning 5 kb 19) . Until now, more than 70 mutations have been re ported in the CYP27B1 gene in multiple ethnic groups 10,14) . Several mutations in the CYP27B1 gene are more common in specific populations 8,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Nishikawa et al 18) presented that liver mitochondrial CYP27A1 can catalyse 1αhydroxyla tion of 25OHD. A little bit increment of 1,25(OH)2D con centrations has been reported in CYP27B1 knockout mice after high vitamin D supplementation, suggesting the con version from 25OHD to 1,25(OH)2D by a nonCYP27B1 enzyme 14) . Wang et al 17) reported two patients with VDDR1A who had normal 1,25(OH)2D values.…”
Section: Case Reportmentioning
confidence: 95%
See 1 more Smart Citation